Evidence for novel genetic loci associated with metabolic traits in Yup'ik people. Issue 5 (1st August 2013) - Aslibekyan, Stella; Vaughan, Laura Kelly; Wiener, Howard W.; Lemas, Dominick J.; Klimentidis, Yann C.; Havel, Peter J.; Stanhope, Kimber L.; O'brien, Diane M.; Hopkins, Scarlett E.; Boyer, Bert B.; Tiwari, Hemant K.
<x xml:space="preserve">Abstract</x> Objectives To identify genomic regions associated with fasting plasma lipid profiles, insulin, glucose, and glycosylated hemoglobin in a Yup'ik study population, and to evaluate whether the observed associations between genetic factors and metabolic traits were modified by dietary intake of marine derived omega‐3 polyunsaturated acids (n‐3 PUFA). Methods A genome‐wide linkage scan was conducted among 982 participants of the Center for Alaska Native Health Research study. n‐3 PUFA intake was estimated using the nitrogen stable isotope ratio (δ15N) of erythrocytes. All genotyped SNPs located within genomic regions with LOD scores > 2 were subsequently tested for individual SNP associations with metabolic traits using linear models that account for familial correlation as well as age, sex, community group, and n‐3 PUFA intake. Separate linear models were fit to evaluate interactions between the genotype of interest and n‐3 PUFA intake. Results We identified several chromosomal regions linked to serum apolipoprotein A2, high density lipoprotein‐, low density lipoprotein‐, and total cholesterol, insulin, and glycosylated hemoglobin. Genetic variants found to be associated with total cholesterol mapped to a region containing previously validated lipid loci on chromosome 19, and additional novel peaks of biological interest were identified at 11q12.2–11q13.2. We did not observe any significant interactions between n‐3 PUFA intake, genotypes, and metabolic traits. Conclusions We have completed a whole genome linkage scan for metabolic traits in Native Alaskans, confirming previously identified loci, and offering preliminary evidence of novel loci implicated in chronic disease pathogenesis in this population. Am. J. Hum. Biol., 25:673‐680, 2013. © 2013 Wiley Periodicals, Inc.